COPD patients prescribed inhaled corticosteroid in primary care: time for re-assessment based on exacerbation rate and blood eosinophils? - Osman Savran; Nina Godtfredsen; Torben Sørensen; Christian Jensen; Charlotte Suppli Ulrik (Respiratory Research, 2021)
Abstract Background and objective Inhaled corticosteroid (ICS) therapy for COPD should be guided by exacerbations and blood-eosinophils according to the GOLD 2020 strategy document. In the present study, we applied these recent recommendations in a large cohort of COPD patients recruited from general practice. Methods The participating general practitioners (n = 144) recruited patients with a diagnosis of COPD currently prescribed ICS and reported data on exacerbation history and blood-eosinophils. Clinical variables were compared using two-sample t-tests. Results The study cohort comprised 1,567 COPD patients (44% males and mean age 72 years). In the past 12 months, 849 (54%) of the COPD patients currently prescribed ICS had no exacerbation, whereas 383 (24%) and 328 (21%) patients, respectively, had a history of one exacerbation and two or more exacerbations. Compared to patients with one or no exacerbation, patients with ≥ 2 exacerbations (21%) per year reported more dyspnea (p < 0.001) and had higher degree of airflow obstruction (p < 0.001). Among patients with no and at least one exacerbation within the preceding 12 months, 30% and 26%, respectively, had a blood-eosinophil count ≥ 0.3 × 109/L. In patients with two or more exacerbations within the last 12 months, 77% had a blood-eosinophil count of ≥ 0.1 × 109/L. Furthermore, 166 patients (11%) had at least one hospital admission due to COPD exacerbation, and a blood-eosinophil count of ≥ 0.1 × 109/L. Conclusion This study of a large cohort of COPD patients currently prescribed inhaled corticosteroids suggests the need for re-evaluating the management strategy to increase benefit and reduce adverse effects of ICS treatment in COPD patients managed in primary care.